Radiation induced cardiotoxicity in left sided breast cancer - Where do we stand? - Pamela Alice Kingsley; Preety Negi (Wolters Kluwer Medknow Publications, 2015)
Breast cancer is the commonest cancer in women, with around a million new cases diagnosed each year worldwide. Adjuvant radiotherapy (RT) is an important component of therapy for many women with early-stage breast cancer. With improving survival rates following breast cancer, patients are increasingly likely to die of other causes. As a result, long-term adverse effects of treatment are of major concern. To determine which treatment is optimal, clinician need to be aware of long-term risks and benefits of adjuvant therapies. An awareness of the potential cardiotoxicity of RT led to the application of improved RT techniques that minimize the irradiation to the heart. Although new techniques, including intensity-modulated RT combined with free breathing gating and helical tomotherapy may further reduce radiation-induced cardiac toxicities, the most important factors in limiting cardiac radiation are associated with the techniques used and the skill of the radiation oncologist.